Effect of Monotherapy with Methotrexate, Etanercept and their Combination on the Quality of Life in Children with Early and Late Juvenile Idiopathic Arthritis: A Prospective Study - Anna N. Fetisova; Tatyana M. Dvoryakovskaya; Vladislav V. Chernikov; Irina V. Vinyarskaya; Rina V. Denisova; Margarita A. Soloshenko; Ksenia В. Isaeva; Anna V. Mamutova ("Paediatrician" Publishers LLC, 2018)
Background. An important goal of treating patients with juvenile idiopathic arthritis (JIA) is to achieve the best quality of life associated with health. Objective. Our aim was to assess the impact of methotrexate plus etanercept therapy on the quality of life of patients with early and late JIA. Methods. The prospective study included patients with early and late JIA without systemic manifestations. The patients' quality of life was assessed with the help of questionnaires for children and parents: the Pediatric Quality of Life Inventory (PedsQL) Generic Core Scale, the Pediatric Quality of Life Inventory (PedsQL) Rheumatology Module, and the Health Utilities Index Mark 3 (HUI3). The quality of life was assessed prior to the therapy and after one, six, and 12 months of treatment. Results. 150 children with JIA aged 5.1 (2.0; 17.7) years; 50 children aged 4.0 (2.3-11.4) years in the group of etanercept monotherapy, 50 children aged 5.0 (3.2-9.0) years in the group of methotrexate monotherapy, and 50 children aged 9.9 (6.4-13.0) years in the group of methotrexate plus etanercept combination therapy. All groups showed low scores on all questionnaires before treatment, compared to healthy children. In the course of therapy, there was a tendency for score increase to almost 1.0 according to the HUI3 questionnaire in all groups. After one year of etanercept therapy, the parameters of the quality of life of children with early JIA did not differ from healthy children; the score increased from 56 to 90 p = 0.942 according to the physical functioning scale and from 60 to 85 p = 0.889 according to the emotional functioning scale. In the 2nd group, there was a tendency for score increase, but a statistically significant difference was found across all scales of the questionnaire. After 12 months of etanercept plus methotrexate combination therapy in patients with late JIA, the questionnaire analysis showed that the responses of healthy children and children with JIA differed with probability p = 0.001 for the physical functioning scale, p = 0.001 for the social functioning scale, p = 0.001 for role functioning, and p = 0.001 for the total score. The score increase from 60 to 85 p = 0.789 was noted for emotional functioning scales. Conclusion. The use of questionnaires to assess the quality of life in children with severe chronic diseases can significantly improve the efficacy of treatment and ensure its control.